DESIGN OF LATVIAN METAL MUSIC ALBUM COVERS IN 2019 - Gusans, Ingars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Latvian metal music has a small but stable place on the map of the metal music world. Each year several music albums of this genre are issued in Latvia. With the decrease in demand for physical data storage devices, brochures and well designed back covers are no longer popular; however the only remaining album cover has gained even more importance – the image, photograph, picture that represents the musical material and acts either as a reflection of the content or as an element for attracting attention and is published on the Internet as well as in printed press as a concrete symbol of the album. The research aim is to describe the design of Latvian metal music album covers in 2019 in the visual context of the albums issued in the world. The research was conducted using the comparative method, looking for the local and global, the typical and different in the visualisation of album covers on the basis of not only theoretical literature but also the many years of experience of the author as a musician and a collector of music records. In general, the visual look of album covers issued in Latvia is typical for heavy metal music and fits in with the visual design of metal band albums in the rest of the world. However, there have been attempts to include eye-catching accents using national or pseudo-national elements or colours.